Biochemical Profiling of Resistant Phenotypes Against Bipolaris oryzae Causing Brown Spot Disease in Rice - Ashfaq, Benish; Arshad, Hafiz M. Imran; Atiq, M.; Yousaf, Sumaira; Saleem, Kamran; Arshad, Amna (Frontiers in Agronomy, 2021)
Brown leaf spot disease of rice is a dominant lethal disease, caused by the fungus Bipolaris oryzae. The pathogen is an obligate parasite and causes qualitative and quantitative damage to rice crop. The objective of the present study was to investigate what extent the defense related biochemical compounds reflect the distinct categories of resistance phenotypes in rice against brown spot disease. This was done by determining the concentration of Catalase (CAT), Phenylalanine ammonia-lyase (PAL), Polyphenol oxidase (PPO), Peroxidase (POD) and β-1,3-Glucanase enzyme in resistant, moderately resistant and susceptible rice genotypes. The disease resistant phenotypes in rice line (PARC-7) reflect the higher accumulation of CAT, PAL, PPO, POD and β-1,3-Glucanase. The pattern of enzyme accumulation was similar in all resistant genotypes. The rice genotypes with moderately resistant phenotypes showed significant difference with respect to the concentration of biochemical defense-related compounds. The difference in accumulation of defense related enzymes reflected the level of disease severity (% leaf area covered) on resistant and moderately resistant genotypes. The susceptible rice genotypes showed the minimum concentration of these enzymes, with the lowest concentrations found in the rice variety Bas-2000 (80% Disease Index). The differential defense response in resistant and susceptible genotypes suggests that these enzymes can be used as biochemical markers to detect disease-resistant genotypes. The study of enzyme accumulation at different time points and at different levels of disease severity resolve the resistance mechanisms against brown spot disease in rice.